Septicemia after chemotherapy for childhood acute lymphoblastic leukemia in China: A multicenter study CCCG‐ALL‐2015. (28th January 2020) - Zhu, Yiping; Yang, Rong; Cai, Jiaoyang; Yu, Jie; Tang, Yanjing; Chen, Yumei; Wang, Ningling; He, Hailong; Wu, Xuedong; Cheng, Frankie W. T.; Sun, Lirong; He, Yingyi; et al.
Abstract: Background: Septicemia is an important cause of treatment‐related mortality and treatment failure in pediatric acute lymphoblastic leukemia (ALL) in developing countries. A multicenter CCCG‐ALL‐2015 study was conducted in China and factors associated with septicemia and mortality were studied. Methods: Patients participated in CCCG‐ALL‐2015 study from January 2015 to December 2017 were included. Patients with documented septicemia were identified from the Data Center and additional data were collected. Results: A total of 4080 patients were recruited in the study and 527 patients with septicemia were identified (12.9%, 95% CI 11.9%‐13.9%). The intermediate risk (IR)/high risk (HR) group had significantly higher incidence of septicemia as compared with low risk (LR) group, 17.1% vs 9.1% (OR 2.07, 95% CI 1.71‐2.49, P  < .001). Induction phase was the period with majority of septicemia episodes happened, 66.8% in LR and 56.1% in IR/HR groups. Gram‐positive bacteria accounted for 54.1%, gram‐negative bacteria 44.5%, and fungus 1.4% of positive cultures. Multidrug‐resistant organisms were detected in 20.5% of all organisms. The mortality rate after septicemia was 3.4% (95% CI 1.9%‐4.9%). Multiple logistic regression identified female gender, comorbid complications, and fungal infection as risk factors associated with mortality. Gram‐negative septicemia was associated with higher mortality, 4.9% vs 1.4% (OR 0.28, 95% CI 0.09‐0.88, P  = .02). There was marked variation in the incidence of septicemia among the 18 centers, from 4.8% to 29.1%. Conclusion: Overall the incidence and pattern of septicemia in this multicenter study in China was similar to the reports of western countries. The septicemia‐related mortality rate was low. There was marked variation in the incidence of septicemia among the centers. Abstract : The incidence and pattern of septicemia in this multicenter study in China was similar to reports of western countries. The septicemia related mortality rate was low. There was marked variation in the incidence of septicemia among the centers.